Research progress on the consistency and evaluation factors of cervical lymphatic metastasis in early tongue cancer - ZHANG Haifeng; NAN Xinrong; HUA Yongqing (口腔疾病防治, 2020)
Early tongue cancer is more prone to occult lymphatic metastasis than other oral cancers. Therefore, the decision of whether to perform neck dissection in the early stage of tongue cancer has been a controversial issue among many scholars. To accurately evaluate the neck condition of patients and determine whether neck dissection should be performed, this article reviews evaluation factors such as sex, age, tumor site, preoperative auxiliary examination results, depth of invasion, pathological grade, and nerve, lymphatic and vascular invasion. A literature review showed that the cervical lymphatics of early tongue cancer mainly migrated to regionsⅠ,Ⅱ and Ⅲ, and distant metastasis was rare. The cervical lymphatics of early tongue cancer were mainly affected by the depth of invasion, pathological grade, and nerve, lymphatic and vascular invasion. To achieve a high survival rate for patients with early tongue cancer, patients with preoperative ultrasound or MRI showing a tumor invasion depth of more than 5 mm, a tumor with a higher pathological grade, and clinical symptoms such as numbness or pain who are in stage T1 and T2 and who have already have nerve and vascular lymphatic infiltration according to the frozen sectioning results should be considered for primary simultaneous cervical lymphatic dissection.